A brief review of the genus Mantura Stephens, 1831 (Coleoptera: Chrysomelidae: Galerucinae: Alticini) of Russia and some adjacent territories - М.Ye. Sergeev (Кавказский энтомологический бюллетень, 2020)
Seven species of the genus Mantura Stephens, 1831 are reviewed. In total, six species are known in Russia. Mantura rustica (Linnaeus, 1767), M. chrysanthemi (Koch, 1803), M. pallidicornis (Waltl, 1839) and M. cylindrica Miller, 1881 are distributed in the European part of the country. One European species, Mantura obtusata (Gyllenhal, 1813) needs verification for distribution in Russia. Two species, M. japonica Jacoby, 1885 and M. clavareaui Heikertinger, 1912 are recorded for the fauna of Russia for the first time. Both species were collected in the Russian Far East, the first one in Primorsky Region, the latter on Sakhalin. The genus Mantura is newly recorded from Sakhalin Island. Key to species of Mantura of the Russian fauna is given